The Influence of Social Media Marketing, Access to Money, Perceived Behavioral Control, Price Perception, and Product Perception on Property Purchase Intention in Jabodetabek - Naufal Afiqusholih Aprinuryanto; Rizal Edy Halim (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the factors influencing property purchase intention among consumers in the Jabodetabek area (Jakarta, Bogor, Depok, Tangerang, and Bekasi), Indonesia’s largest property market. The research integrates the Theory of Planned Behavior (TPB) with external variables such as access to money, perceived behavioral control, physical quality perception, price perception, and social media marketing activities. A quantitative approach was employed using an online survey method, and data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all five independent variables significantly influence property purchase intention. This study contributes both theoretically by reinforcing TPB in the context of real estate consumer behavior and practically by offering strategic recommendations for developers to enhance consumer engagement through digital marketing, transparent pricing justification, and improved physical product quality.